Understanding theology and popular culture - Lynch, Gordon, 1968- (Malden, MA : Blackwell Pub., 2005)
"Understanding Theology and Popular Culture" is one of the first books to give an overview of the key issues and methods in this field of study. This title provides a detailed introduction to key theories and debates in popular cultural studies. It presents a reasoned argument about the distinctive contribution that theology can make to the study of popular culture. It is illustrated through a range of original case studies, from Eminem to The Simpsons. It is suitable for both beginning students and more advanced researchers. The author has created the Theology and Popular Culture Gateway which is one of the first academic Internet gateways for the study of theology and contemporary culture
What is 'popular culture'? -- Why should theologians and scholars of religion study popular culture? -- Machines, TVs, and shopping : the shape of everyday life in contemporary western society -- Can popular culture be bad for your health? -- Developing a theological approach to the study of popular culture -- An author-focused approach to studying popular culture : Eminem and the redemption of violence -- Text-based approaches to studying popular culture : 'Homer the heretic' and civil religion -- An ethnographic approach to studying popular culture : The religious significance of club culture -- Taking steps towards a theological aesthetics of popular culture
Includes bibliographical references (pages 213-230) and index
Keywords: Christianity and culture; Theology; Theology